A Giant Bulk‐Type Dresselhaus Splitting with 3D Chiral Spin Texture in IrBiSe. Issue 4 (3rd April 2020) - Liu, Zhonghao; Thirupathaiah, Setti; Yaresko, Alexander N.; Kushwaha, Satya; Gibson, Quinn; Xia, Wei; Guo, Yanfeng; Shen, Dawei; Cava, Robert J.; Borisenko, Sergey V.
Abstract : Non‐magnetic half‐metals are a new class of materials that are metallic only for one spin direction. In contrast to conventional half‐metals, this spin direction is not fixed in space and is always perpendicular to the momentum of an electron. IrBiSe is one of such materials. Using angle‐resolved photoemission spectroscopy and band structure calculations, Zhonghao Liu et al. find a record‐high Dresselhaus spin‐orbit splitting, fully spin‐polarized remnant Fermi surfaces and a chiral 3D spin‐texture, all with no magnetism present (see article number 1900684 ). Promising applications include using IrBiSe as a source of spin‐polarized electrons, and lightly doped IrBiSe is expected to generate electric‐field‐controlled spin‐polarized currents, free from back scattering, and could host triplet superconductivity.